Development of a core outcome set for use in determining the overall success of gastroschisis treatment. Issue 1 (December 2016) - Allin, Benjamin; Ross, Andrew; Marven, Sean; Hall, Nigel; Knight, Marian
Abstract Background Gastroschisis research is limited in quality by the presence of significant heterogeneity in outcome measure reporting (PloS One 10(1):e0116908, 2015). Using core outcome sets in research is one proposed method for addressing this problem (Trials 13:103, 2012; Clin Rheumatol 33(9):1313-1322, 2014; Health Serv Res Policy 17(1):1-2, 2012). Ultimately, standardising outcome measure reporting will improve research quality and translate into improvements in patient care. Methods/design Candidate outcome measures have been identified through systematic reviews. These outcome measures will form the starting point for an online, three-phase Delphi process that will be carried out in parallel by three panels of experts. Panel 1 is a neonatal panel, panel 2 is a non-neonatal panel and panel 3 is a lay panel. In round 1, experts will be asked to score the previously identified outcome measures from 1–9 based on how important they think the measures are in determining the overall success of their/their child's/their patient's gastroschisis treatment. In round 2, experts will be presented with the same list of outcome measures and with graphical representations of how their panel scored that outcome in round 1. They will be asked to re-score the outcome measure taking into account how important other members of their panel felt it to be. In round 3, experts will again be asked to re-score each outcome measure, but this time they will receive a graphical representation of the distribution of scores from all three panels which they should take into account when re-scoring. Following round 3 of the Delphi process, 40 experts will be invited to attend a face-to-face consensus meeting. Participants will be invited in a purposive manner to obtain balance between the different panels. The results of the Delphi process will be discussed, and outcomes re-scored. Outcome measures where > 70 % of the participants at the meeting scored them as 7–9 and < 15 % scored them as 1–3 will form the core outcome set. Discussion Development of a core outcome set will help to reduce the heterogeneity of the outcome measure reporting in gastroschisis. This will increase the quality of research taking place and ultimately improve care provided to infants with gastroschisis.